7 - Horton Revisited: African Traditional Thought and Western Science - Keita, Lansana (Africa Development, 2021)
Over the years Robin Horton has argued for what he refers to as the ‘continuity thesis’ according to which there are theoretical similarities between African tra- ditional thought and modern Western science. Horton’s thesis stands in contrast to the standard Western anthropological appraisal of traditional African thought. The standard appraisal (Levy-Bruhl, Durkheim, Evans-Pritchard, et al.) stated that the two modes of thought were incommensurate. I argue that while the continuity thesis holds for certain aspects of African thought – empirical, proto- scientific and metaphysical – it does not apply to traditional African religious expression. My thesis here is that belief systems founded on magic, religion and their combinations should be understood as belonging to what might be referred to as general metaphysics. I argue too that if the continuity thesis is to apply to the history of thought in Africa then the more apt comparison should be between the different phases of technological and scientific thought of the West. Thus Horton’s claim that traditional African religious thought is configured accord- ing to the goals of explanation, prediction and control thereby putting it on the same epistemic plane as modern Western science is thereby rendered irrelevant. On the other hand the goal of traditional African religion like that of many other religious traditions – including those of the West – has principally been to seek a conscious communion with ancestors and anthropomorphised godheads and spiritual entities of the metaphysical realm. Lansana Keita, University of the Gambia, The Gambia and BARA, University of Arizona, USA.